Effects of fermented soybean residues on the growth performance, serum indexes, and digestive performance of Xianju chickens - JIANG Lai; YAO Lei; YUAN Chunchun; YE Wenxin; FAN Jinghui; QIAN Lichun (浙江大学学报. 农业与生命科学版, 2023)
This study aims to use microbial fermentation technology to improve the utilization of soybean residues and to develop a new type of fermented feed with superior quality and competitive price. In this experiment, fermented soybean residues were used to feed 1 day-of-age Xianju chickens, lasting for 42 d. Five groups were set up, including the control group T1, fed with the basal diets; the antibiotic group T2, fed with the basal diets supplemented with 40 mg/kg methylene salicylic acid bacitracin; the treatment groups T3, T4, and T5, fed with the basal diets in which 2%, 4%, and 6% soybean meal were replaced by fermented soybean residues, respectively. The results were shown as follows. 1) Compared with the control group T1, the 42 day-of-age body mass and average daily gain of Xianju chickens were significantly higher in each group, and the feed to gain ratio was significantly lower in T4 group (P＜0.05). 2) Compared with the control group, the albumin content was extremely significantly higher in T4 group (P＜0.01), and the superoxide dismutase activity was extremely significantly higher in T2 and T5 groups (P＜0.01), while the malondialdehyde content was extremely significantly lower in T2 group (P＜0.01). 3) Compared with the control group, the apparent digestibility of crude protein and crude fiber was significantly increased in T4 group (P＜0.05) and the apparent digestibility of crude protein was extremely significantly increased in T5 group (P＜0.01); the duodenal amylase activity in T4 group (P＜0.05), the duodenal protease activities in T4 and T5 groups (P＜0.01), and the chymotrypsin activities in T2, T3, and T5 groups (P＜0.05) were significantly improved. In conclusion, replacing 4% soybean meal in the basal diets with an equal amount of fermented soybean residues has the best feeding effect, which could significantly promote the growth performance, apparent digestibility of crude protein and crude fiber, and digestive enzyme activities in vivo of Xianju chickens, improve their serum indexes, and has the potential to replace antibiotics.